Prostitution : prevention and reform in England, 1860-1914 - Bartley, Paula (Women's and gender history., 2000)
The first comprehensive overview of attempts to eradicate prostitution from English society, including discussion of early attempts at reform and prevention through to the campaigns of the social purists.